Employing Descriptive and Parametric Statistics to Analyse Entrepreneurship Opportunity As A Catalyst For Youth Employment - Omang, Thomas Achoda (ACEND Foundation, 2021)
The study examines how entrepreneurship opportunities have solved the problem of youth employment and underemployment in Calabar South Local Government Area, Cross River State, Nigeria. Adopting the survey research design, data was gathered from four hundred (400) youths from Calabar using cluster, purposive and simple random sampling techniques. The instrument of data collection is a structured questionnaire. The generated data were appropriately coded and analyzed using simple percentages and Multiple Regression Analysis at a 0.05 level of significance. Results show that an entrepreneurship opportunity significantly solves the problem of youth employment and underemployment in Calabar South Local Government Area, Cross River State, Nigeria. The study recommended, among others, that: Skill acquisition program should be organized periodically where talks on entrepreneurship and practical participation will be carried out. Workshop on capacity building and skill acquisition will go a long way to ensure technological advancement and rapid growth/development of the society